2017
DOI: 10.1111/desc.12567
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the origins of political views: biases in explanation predict conservative attitudes in children and adults

Abstract: We tested the hypothesis that political attitudes are influenced by an information-processing factor - namely, a bias in the content of everyday explanations. Because many societal phenomena are enormously complex, people's understanding of them often relies on heuristic shortcuts. For instance, when generating explanations for such phenomena (e.g., why does this group have low status?), people often rely on facts that they can retrieve easily from memory - facts that are skewed toward inherent or intrinsic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 89 publications
(195 reference statements)
2
26
0
Order By: Relevance
“…Indeed, other programs of research argue that some psychological processes that emerge during childhood shape adult cognition (e.g., Block & Block, 2006;Fraley, Griffin, Belsky, & Roisman, 2012;Heiphetz, Spelke, & Young, 2015;Hussak & Cimpian, 2018). A similar analysis may apply to early-developing punishment concepts.…”
Section: Adults' Punishment Conceptsmentioning
confidence: 95%
“…Indeed, other programs of research argue that some psychological processes that emerge during childhood shape adult cognition (e.g., Block & Block, 2006;Fraley, Griffin, Belsky, & Roisman, 2012;Heiphetz, Spelke, & Young, 2015;Hussak & Cimpian, 2018). A similar analysis may apply to early-developing punishment concepts.…”
Section: Adults' Punishment Conceptsmentioning
confidence: 95%
“…For example, individuals may believe that the rich are wealthy because of their inherent qualities. Studies of children and adults (Hussak & Cimpian, , ) have shown that individuals are more supportive of the status quo when social stratification differences (e.g., the presence of wealth inequalities) were explained with inherent explanations (e.g., one group is smarter than another group) than with extrinsic explanations (e.g., one group happens to live in a town with better jobs).…”
Section: Cognitive Styles and Strategiesmentioning
confidence: 99%
“…Because of its relations with system justification beliefs, the inherence heuristic has implications for the development of political ideologies. Specifically, an individual's reliance on inherent explanations has been shown to predict conservatism, defined as the acceptance of socioeconomic stratification and adherence to tradition (Hussak & Cimpian, ). Although adults sometimes use the inherence heuristic, reliance on the heuristic decreases with age, as adults typically have more detailed explanations of external factors and can manage more cognitive complexity (Cimpian & Steinberg, ).…”
Section: Cognitive Styles and Strategiesmentioning
confidence: 99%
“…Retrospective reports may be too unreliable or our college-age student sample too old to capture the most formative periods of parental influence. Studies including children as young as 3 to 8 years old detected significant associations between parental ideological orientations and children's cognitive preferences for order, conformity, and security, as well as trust and information processing patterns linked to authoritarianism (Guidetti, Carraro, & Castelli, 2017;Hussak & Cimpian, 2018). Parents and children may share other cognitive preferences, such as epistemic and relational needs, or personality traits not examined in this study that predict similarities in political and information processing preferences.…”
Section: Discussionmentioning
confidence: 64%
“…Family communication patterns that predispose children to organize information into an overall "story" structure may therefore shape later information processing and memory patterns. Whether parents offer inherent versus extrinsic explanations for social phenomena such as group disparity can also affect children's ideological orientations and processing preferences (Hussak & Cimpian, 2018). Further, parental behaviors directly related to the provision and use of technology in the household may offer another pathway affecting a child's cognitive skills related to information processing (Helsper & Eynon, 2010).…”
Section: Discussionmentioning
confidence: 99%